2016
DOI: 10.7439/ijbar.v7i6.3325
|View full text |Cite
|
Sign up to set email alerts
|

Perception of medical students on usefulness of interactive lectures: Can it be a welcome change?

Abstract: Background: Interactive lecture is a student centred teaching technique incorporating, multimodal strategies to create more engaging classroom settings. In our medical college, traditional lecture approach has been the core teaching method. So, we intended bringing in a change to passive way of learning by introducing first interactive lecture in Microbiology. The objective of our study was to evaluate perception of students on the usefulness of interactive lecture over traditional lecture. Methods: A session … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We have observed that our 83.3% participants also voted that interactive learning promoted self-learning. In 2016, study conducted by Jayakumare et al 18 found that majority of students (92%) supported that the interactive lectures promoted self-learning. Our observations suggested majority of participant i.e 96.3% believe that classroom collaboration was enhanced.…”
Section: Discussionmentioning
confidence: 98%
“…We have observed that our 83.3% participants also voted that interactive learning promoted self-learning. In 2016, study conducted by Jayakumare et al 18 found that majority of students (92%) supported that the interactive lectures promoted self-learning. Our observations suggested majority of participant i.e 96.3% believe that classroom collaboration was enhanced.…”
Section: Discussionmentioning
confidence: 98%
“…17 In a published research, 94% students reported that interactive sessions facilitate interest in subject and motivate for more study. 18 According to 95% participants of a study, interactive lecture modules were associated with significant improvement in understanding of subject and better practical skills. 19 Many researchers emphasize that interactive environment increases the critical thinking ability and attention span of learner with improved learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted by Jayakumar et al . [ 23 ] (2016) 92% of students agreed that the interactive sessions motivated them to study more and 94% reported that interactive sessions builds their confidence. Our observations are in accordance to the published studies.…”
Section: Discussionmentioning
confidence: 99%